Граматичні відхилення в мові північно-східного діалекту Англії - Колісник, Марина Павлівна; Kolisnyk, M. P. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті на підставі аналізу матеріалів архіву інтерв’ю представників північного сходу Англії «Talk of the Toon» з’ясовано наявність граматичних відмінностей у мовленні носіїв цього діалекту. За ознаками часових проміжків функціонування діалекту, а також статі, віку та соціокультурного рівня його носіїв сформовано матриці частотних показників морфологічних і синтаксичних відхилень північно-східного діалекту. З’ясовано загальну закономірність подальшого розвитку діалекту як складової частини сучасної англійської мови Англії. In the article on the basis of analysis of the data from the interview archive of English north-eastern representatives «Talk of the Toon» the occurrence of grammatical aberrations in the speech of the mentioned dialect speakers was established. With regard for time intervals of the dialect functioning within the historical period of 1960–2000 years as well as gender, age, and dialect speakers’ sociocultural level, the author has built the frequency rates matrix of morphological and syntactical aberrations in the English north-eastern dialect. Examples of interview fragments were provided, the ones containing typical morphological and syntactical aberrations in the speech of dialect speakers. Relative charac¬teristics of the studied aberrations frequency as well as upon the reasons of their origin and functional tendencies in the informants’ speech were given. Further development mechanism of the dialect as a part of English language was forecasted.
Grammatical Aberrations in the Language of English North-Eastern Dialect
Keywords: північно-східний діалект; English north-eastern dialect; аналіз; analysis; морфологічні та синтаксичні особливості; morphological and syntactical characteristics